PENGEMBANGAN SELF REGULATED LEARNING DAN KEMAMPUAN METAKOGNITIFm: SUATU TINJAUAN DETERMINAN - MUTHMAINNAH (POLITEKNIK PIKSI GANESHA, 2018)
This research aims to describe the development of self-regulated learning (SRL) and metacognitive skills with a determinant of emotional support and intrinsic motivation of students in economic subjects ingrade 10 social class at 1 Lembang senior high school. The method used in this research is an explanatory survey. The population in this researchis whole students of grade 10 in social class, with a number of students about283 with the sampling technique usingproportional random sampling. The data used are primary data and secondary data. Primary data were obtained from questionnaires to 165 students assamples. Meanwhile, secondary data obtained from interviews with studentsand website related issues with a general description of the object of research. The data analysis technique using path analysis. The result of the research to conclude the existence of a significant positive effect of emotional support and motivation towards student’s self-regulated learning and metacognitive skills. The greater emotional support and motivation, self-regulated learning and metacognitive skills also getting greater.